CO02 | Hepatic fibrosis as predictor of cancer-associated thrombosis in patients with intrahepatic cholangiocarcinoma (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Cholangiocarcinoma (CCA) is an aggressive malignancy with a steadily increasing incidence worldwide, particularly of the intrahepatic variant (iCCA). Consequently, identifying factors that may modify the natural history of this disease has become the focus of interest in multiple studies. While the relationship between hepatic fibrosis and the development of CCA has been previously explored, the contribution of fibrosis-induced coagulation imbalance to disease progression remains unclear. This study aimed at investigating the relationship between advanced liver fibrosis, hemostasis activation, and occurrence of cancer-associated thrombosis (CAT) in patients with iCCA.